INFLUENCE OF JUDICIAL PROCEDURES OF COMPANY RESCUE ON CONTRACTUAL RELATIONSHIP: IMPORTANCE IN PRESERVING CONTRACTS - Barakauskas, Sigitas (Teisė, 2015)
It is generally acknowledged that viable companies should have an opportunity to get a fresh start or a second chance. Governments are increasingly reforming the regulation in force with a view to giving priority to company rescue and preservation of companies (but not to involuntary liquidation of a company); the new approach of the European Union towards company failures and insolvency is also based on this idea. However, certain regulatory aspects of the judicial procedures of company rescue in a number of countries remain problematic and constitute obstacles to rescue even viable companies. One of such problematic aspects is regulation related to preserving contracts during the judicial procedures of company rescue. The success of company rescue process greatly depends on ensuring continuity of contracts. However, the regulation existing in most of the countries that are analyzed in this article (i.e. Great Britain, Germany and Lithuania, except for France) does not create appropriate conditions for ensuring stability of contractual relationship and therefore requires improvement. It needs to be noted that the greatest threat to the stability of the contractual relationship during the rescue procedure is posed by ipso facto provisions. Ipso facto provisions can prejudice the interests of both a company being rescued and stakeholders who are interested in rescue of the company because these provisions may become an obstacle to rescue even viable companies. Therefore, in order to avoid this and to facilitate the preservation of viable companies, legislation governing company rescue should provide for the prohibition of ipso facto provisions. In addition to this, such legislation should also provide for adequate protection of the legitimate interests of the contractors who will be forced to continue to fulfil their obligations, which they assumed before the beginning of the rescue procedure, during the rescue procedure.